1994
DOI: 10.1182/blood.v83.10.2809.2809
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of chromosome 20q in myelodysplasia can occur in a multipotent precursor of both myeloid cells and B cells

Abstract: Deletions of the long arm of chromosome 20 are associated with several myeloid malignancies and, in particular, with myeloproliferative disorders and myelodysplastic syndromes (MDS). Together with deletions of chromosome 5q and chromosome 7q, chromosome 20q deletions have previously been thought to be restricted to myeloid cells in patients with MDS. We report here that deletion of chromosome 20q in MDS can arise in a multipotent precursor of both myeloid cells and B cells. Clonal Epstein-Barr virus (EBV)-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…The XCI patterns of CD19 þ B cells were similar to T cells except in two patients (one RA, one CMML) with monoclonal B and polyclonal T lymphopoiesis. This suggests clonal involvement of an MDS progenitor cell common to the myeloid and B-lymphocytic lineages, a finding that has been previously reported to occur in MDS (Raskind et al, 1984;Lawrence et al, 1987;White et al, 1994;Van Lom et al, 1995). Since there is growing evidence that there is an increased association between MDS and lymphoid malignancies (Copplestone et al, 1986;Mitterbauer et al, 1997), our clonality results can also be explained by the concomitant occurrence of MDS and another clonal B-cell disorder.…”
Section: Discussionsupporting
confidence: 67%
“…The XCI patterns of CD19 þ B cells were similar to T cells except in two patients (one RA, one CMML) with monoclonal B and polyclonal T lymphopoiesis. This suggests clonal involvement of an MDS progenitor cell common to the myeloid and B-lymphocytic lineages, a finding that has been previously reported to occur in MDS (Raskind et al, 1984;Lawrence et al, 1987;White et al, 1994;Van Lom et al, 1995). Since there is growing evidence that there is an increased association between MDS and lymphoid malignancies (Copplestone et al, 1986;Mitterbauer et al, 1997), our clonality results can also be explained by the concomitant occurrence of MDS and another clonal B-cell disorder.…”
Section: Discussionsupporting
confidence: 67%
“…16 On the other hand, in vitro, both anti-CD38-and del 20q-positive cells were observed in the Epstein-Barr virus-transformed lymphoid cell line from the cells of a del 20q-MDS case. 17 These reports might indicate that the del 20q-associated cytogenic finding is associated with a chromosomal abnormality related to not only myeloid but also other lineages. Alternatively, MDS with Bcell abnormality might be related to a viral infection such as Epstein-Barr virus.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, a deletion of human chromosome 20q involving the region in which the C/EBP[3 gene maps has been reported in several cases of myeloproliferative disorders and myelodisplastic syndromes (14), and in 16 out of 68 patients (24%) affected by myeloid leukemia (15). It has also been shown that such a deletion in myelodysplasia can arise in a multipotent precursor of both myeloid and B cells, suggesting that this mutation can cause a disease arising in a cell with both myeloid and lymphoid potential (16). These reports together with our observation of abnormal proliferation in both myeloid and B cell compartments in C/EBP[3-/-mice, suggest that inactivation of the C/EBP[3 gene could represent a link between myelo-and lympho-proliferative disorders.…”
Section: Discussionmentioning
confidence: 99%